Biomimetic application of desert ant visual navigation for mobile robot docking with weighted landmarks. (6th July 2005) - Wei, Ran; Austin, David; Mahony, Robert
Previous work has shown that honeybees use a snapshot model to determine a local vector to find their way home. A simpler, average landmark vector model has since been proposed for biologically-inspired mobile robot homing. Previously, the authors have extended the model to address the problem of docking a unicycle-like vehicle smoothly using bearing-only information and without reconstructing the pose of the vehicle (Wei et al., 2003, 2004). Here, we extend further to consider weighted landmarks, allowing greater control over the shape of the trajectory that the robot will follow. This approach permits docking from a wider range of initial poses, while respecting the kinematic constraints of the robot. The proposed control method has been implemented on the Nomadic Technologies XR4000 robot at ANU using visual landmarks. Experimental results are presented which demonstrate the desired docking behaviour from a broad range of initial conditions.